Influência de fungos micorrízicos arbusculares como promotores de crescimento de porta-enxertos de citros - Miranda, Priscila Batista (2017)
Plant growth promoting microorganisms have been widely used in agriculture. As an example, the arbuscular mycorrhizal fungi, which associate with the roots of plants and help them in the better absorption of nutrients and water, have been widely used as biological input in several studies. However, their use is mostly associated with phosphorus addition, and it is also important to carry out studies evaluating the isolated effect of these microorganisms and the dependence of the plants on them. The objective of this work was to verify the effect of the mycorrhizal association of Glomus clarum and G. etunicatum on the initial growth of rootstocks: Rangpur lime, Swingle Citrumelo and Tangerine Sunki. The experimental design was completely randomized with a 3 x 4 factorial arrangement, with 5 replications, corresponding to 3 rootstocks, 4 managements (mineral fertilization, inoculation with G. clarum or G. etunicatum and control). The inoculation with mycorrhizal fungi and fertilization with P were performed simultaneously and before the sowing, respectively. In addition, after germination, N and micronutrients were applied by the irrigation water. The following parameters were evaluated: height, stem diameter, number of leaves, shoot dry mass, colonization and mycorrhizal dependence and the macro and micronutrients content from shoots. There was a significant interaction between the rootstocks and treatments applied in this study for most of the evaluated variables. The highest values of height, leaf number and dry mass of the aerial part were provided by the mineral fertilization management. Rangpur lime and Swingle Citrumelo obtained higher height. The largest diameter of the stem was reached by Swingle Citrumelo and the management that provided the largest diameter was inoculation with G. etunicatum. Rangpur lime presented moderate mycorrhizal dependence for G. clarum and marginal for G. etunicatum, while the other rootstocks present marginal dependence on the two microorganisms. There was a low percentage of mycorrhizal colonization in the rootstocks. There was a significant interaction between the rootstocks and the applied managements, and mineral fertilization provided higher levels of N, P, Ca and S to the plants. Regarding the micronutrients, mineral fertilization also excelled in the absorption of B, Cu, Fe, Mn and Zn. G. clarum presented values of Cu, Mn and Zn higher than the control. However, considering all the evaluated parameters, the management through the use of mycorrhizal fungi was not satisfactory, the best result was obtained with mineral fertilization, such effect can be justified by the high content of P in the substrate, which can be affected the efficiency of mycorrhization.